1962 Meletean - University of Wisconsin-River Falls (University of Wisconsin-River Falls, 1962)
Online, digitized version of the Wisconsin State College, River Falls yearbook for 1962. The 1962 Meletean includes 192 pages of text and photographs. The 1962 yearbook is also known as the Fiftieth Anniversary Meletean. This digital copy was created by Pang Thao in 2012.
Meletean 1962
50th Meletean
192 p. divided into 5 parts: Part 1 = Cover and Pages 1-25; Part 2 = Pages 26-57; Part 3 = Pages 58-107; Part 4 = Pages 108-127; Part 5 = Pages 128-192 and Back Cover. Part 1 contains the introduction and photographs; Part 2 contains photographs of the Administration, Faculty and Staff and photographs of Special Events; Part 3 contains photographs and descriptions of Organizations on campus; Part 4 contains photographs and a description of Athletics on campus; and Part 5 contains individual Class photographs and a section on "Campus Life and the Meletean, 1912-1962." Editor: Nancy MacNeil. Art Editors: Barbara Johnson and Mary Johnson. Sports Editors: Lance Hittman and Gordon Graham. Organizational Editors: Mary Ann Loyas, Stephanie Baker and Diane Fansler. Assistant Editors: Kristin Engebreth, Fran O'Connell and Keith Olsen.
Keywords: Yearbook; Class of 1962 yearbook; School yearbooks--Wisconsin--River Falls; Fiftieth anniversary Meletean; 1962 yearbook; University of Wisconsin-River Falls--Students--Yearbooks; College yearbook; 1962 year book; University year book; Class of 1962 year book; Year book; University yearbook; College year book